Novel prognostic histopathological grading system in oral squamous cell carcinoma based on tumour budding and cell nest size shows high interobserver and intraobserver concordance. Issue 4 (8th December 2018) - Boxberg, Melanie; Bollwein, Christine; Jöhrens, Korinna; Kuhn, Peer-Hendrik; Haller, Bernhard; Steiger, Katja; Wolff, Klaus-Dietrich; Kolk, Andreas; Jesinghaus, Moritz; Weichert, Wilko
Abstract : Aims: Squamous cell carcinoma of the oral cavity (OSCC) is a common tumour entity with a variable, partially highly aggressive clinical course. Recently, we proposed a novel (three-tiered) clinically useful grading scheme strongly associated with patient outcome in OSCC, consisting of a sum score of the histomorphological patterns tumour budding and cell nest size which outperforms WHO based grading algorithms currently in use. The aim of our study was to probe for interobserver and intraobserver reliability of this novel grading system. Methods: 108 OSCC were retrospectively scored according to the proposed grading scheme by three independent pathologists—two experienced head and neck pathologists and one pathologist in training—blinded to each other's scoring results. Results: The Cohen's Kappa ( κ ) values for concordance rates between experienced pathologists were κ =0.97 for the overall grade, κ =0.97 for budding activity and κ =0.91 for cell nest size, indicating a strong interobserver reliability of our proposed grading system. Initial interobserver agreement was markedly lower with the pathologist in training ( κ =0.55 for overall grade) but improved significantly after a training session ( κ =0.87 for overall grade). Intraobserver concordance was high ( κ =0.95 for overall grade), indicating a high reproducibility of the algorithm. Conclusions: In conclusion, our study indicates that OSCC grading based on our proposed novel scheme yields an excellent inter-reader and intrareader agreement, further supporting the suitability of this grading system for routine pathological practice.